Measuring the process efficiency of controlled gas metal arc welding processes - Pepe, Nuno; Egerland, Stephan; Colegrove, Paul A.; Yapp, David; Leonhartsberger, Andreas; Scotti, Ameirico (Cranfield University, 2011)
The thermal or process efficiency in gas metal arc welding (GMAW) is a crucial input to numerical models of the process and requires the use of an accurate welding calorimeter. In this paper, the authors compare a liquid nitrogen calorimeter with an insulated box calorimeter for measuring the process efficiency of Fronius cold metal transfer, Lincoln surface tension transfer and RapidArc, Kemppi FastRoot and standard pulsed GMAW. All of the controlled dip transfer processes had a process efficiency of ∼85% when measured with the liquid nitrogen calorimeter. This value was slightly higher when welding in a groove and slightly lower for the RapidArc and pulsed GMAW. The efficiency measured with the insulated box calorimeter was slightly lower, but it had the advantage of a much smaller random erro